Understanding Educational Games Culture in Extending the Relationship between Graphic Appearance and Experiences among Malaysian Lower Secondary - Lee, Lilian Shiau Gee; Jasni Dolah; Norfarizah Mohd Bakhir (EDP Sciences, 2018)
Educational games provide a virtual environment for the students, particularly in an endeavour to increase student immersion, and this need of students satisfied with the visual aspect conditions of the game screen to go to the following stage. In determining the effect of visual design on students' learning experiences - it’s required a further analysis within the students' motivation, engagement and enjoyment. To achieve this goal, a solid fundamental understanding in theoretical philosophy, which closely related to describe the relationship of visual experience, especially in intrinsic tendencies theory and visual principles that on holds the context of motivation, engagement and enjoyment among students. In this regard, a thorough discussion of relevant theories were led to the suggestion theoretical framework and proposed of Experience Based Design Graphic Style (EBDGS) to identify student’s experiences (motivation, engagement and enjoyment) outcomes which mostly depends on the visual design approaches to designing the game scenarios. This paper also aims to describe the theoretical framework proposed in understanding the Malaysian student experience’s outcomes by placing the abstract style and realistic style in developing Experience Based Design Graphic Style (EBDGS) game prototype: EBGDS A (Abstract) and EBGDS R (Realistic). The implication of the theoretical framework was focused on the visual design (graphic styles) of games that intentionally centred in the students’ experience that tied to the demographic factors (gender, type of schools and areas), and the resulting experiences are examined through the Student Experience in Graphic Measurement Scale (SEIGMS). The intention of this research not only emphasize the suitability visual appearance able better improve student experiences but also increases deeper local knowledge in visual design guidelines in educational game design contexts.